Evaluating Historical CGER Assessments : How Well Have They Predicted Subsequent Exchange Rate Movements? - Lee, Jungjin (IMF Working Papers; Working Paper, 2009)
The IMF's Consultative Group on Exchange Rate issues (CGER) has been conducting exchange rate assessments as part of the surveillance process since 1997. This paper evaluates CGER assessments from 1997 to 2006, by comparing these to subsequent movements in real effective exchange rates (REER). We find that CGER's estimated misalignments have predictive power over future REER movements, especially over longer horizons and after changes in fundamentals are accounted for. But while CGER misalignments frequently predict the direction of currency movements correctly, misalignments have tended to be persistent, resulting in systematic errors-overprediction for undervalued currencies and underprediction for overvalued currencies.